Synthesis And Spectroscopic Studying of New Azo Ligand From 2-Naphthol Derivative And It’s Complexes With Some Transition Metal Ions - M.alabidi, Hawraa; M.alabidi, Ali; F Makki, Nahlah (Al-Qadisiyah Journal of Pure Science, 2018)
This work deals with the preparation and identification of new azo ligand as A derivative of 2- Naphthol and It’s Complexes with Co(II),Ni(II),Cu(II) and Ag(I) ions. The characterization of this ligand was done 1H-NMR,13C-NMR,Uv-Vis and FTIR spectra .The complexes preparation were performed after fixing the optimum conditions of pH and molar concentration using Uv-Vis spectra of mixed solutions of the above ions with azo ligand .A wide range of pH and molar concentration obeyed lambert-Beers Law were studies , and the stability constant has been founded at optimum conditions of pH ,mole ratio for all complex. Spectrophotometric studies such as IR and Uv-Vis and the molar conductivity of these complexes were used to determine the molecular formulas of the ligand and complexes.